Structural characteristics of fucoidanases from marine microorganisms - Huynh, Hoang Nhu Khanh; Vo, Thi Dieu Trang; Cao, Thi Thuy Hang (Vietnam Journal of Biotechnology, 2025)
Fucoidanase is an enzyme that catalyzes the degradation of fucoidan, a complex sulfated polysaccharide found in brown algae, through the hydrolysis of glycosidic bonds between fucose units. This enzyme plays a crucial role in harnessing and optimizing the biological applications of fucoidan, such as immune support, anti-cancer properties, and anti-inflammatory effects. Marine microorganisms are considered a rich source of fucoidanases due to their adaptation to fucoidan-rich environments. This report focuses on the relationship between the structure of fucoidanases from marine microorganisms and its catalytic function on fucoidan substrates, including the active site with conserved amino acids essential for substrate binding, domain structures that facilitate fucoidan recognition, and the enzyme’s selectivity for specific glycosidic linkages. Studies on the tertiary and quaternary structures reveal that the enzyme's spatial configuration not only enables precise fucoidan binding but also ensures stable activity in marine environments. Furthermore, comparative analysis of fucoidanases derived from different marine bacterial strains reveals structural variations that influence their substrate specificity and catalytic efficiency. Notably, the presence of calcium ions (Ca²⁺) has been shown to play a significant role in stabilizing the enzyme’s three-dimensional conformation, maintaining its catalytic integrity, and enhancing its activity under saline conditions commonly found in marine ecosystems. Calcium-binding motifs observed in some fucoidanase structures may also contribute to maintaining structural rigidity, thus improving resistance to denaturation and extending the enzyme’s functional lifespan. Recent advancements in protein modeling and molecular docking have contributed to a deeper understanding of how Ca²⁺ interacts with the enzyme and supports substrate recognition. These insights pave the way for future enzyme engineering efforts aimed at improving fucoidanase stability, activity, and industrial applicability in the production of bioactive oligosaccharides.